Kinerja Karyawan Dilihat Dari Pengaruh Program Pelatihan dan Motivasi Kerja di Hotel The Seminyak Beach Resort & Spa - I Made Agus Sugana Nugeraha; I Made Gede Darma Susila; Ida Ayu Anggreni Suryaningsih; Ni Nyoman Ayu Suriyani (Universitas Triatma Mulya, 2026)
In the hospitality sector, service quality depends heavily on how well employees perform, and that concern is the starting point for this study, focused on a resort environment The Seminyak Beach Resort & Spa where guest expectations keep climbing while staff performance still varies. Three theoretical lenses shape the analysis: Mangkunegara on training, Robbins and Judge on work motivation, and Sutrisno on employee performance; together they form a conceptual model connecting training and motivation to performance outcomes. Using a quantitative, causal-associative design, the study surveyed the entire workforce 185 employees at The Seminyak Beach Resort & Spa through total sampling. Questionnaires built on a Likert scale served as the main data source, complemented by observation, interviews, and documentation; SPSS 26 was then used to run instrument tests, classical assumption tests, multiple linear regression, correlation analysis, t-tests, F-tests, and the coefficient of determination. Both training and work motivation turned out to have a positive, significant effect on performance individually, and a significant combined effect as well, jointly explaining 55.3% of the variance (R Square = 0.553). The clear implication: sharpening training quality and sustaining strong work motivation are the two levers most likely to lift employee performance at The Seminyak Beach Resort & Spa.